Projects and Environments: Recursive Socio-Historical Realities (Revista LIDER, 2018)
This study seeks to make an epistemological analysis of the relationships between environment and society, critically conceptualizing the terms "environment" and "human projects". Our inquiry emphasizes that the environment and human projects are not isolated units, and should be thought of in the context of their circumstantial and historical interrelations and inderdependencies, that is, within the framework of their specific dialogical and recursive conditions. The study shows that both, “environment" and "human projects”, tend to integrality, interact and condition each other, therefor they share recursive relations.